Repair of temporary fixed dental prostheses using a flowable resin composite: Effect of material, bonding, and aging - Ruwaida Z. Alshali; Dalea M. Bukhary; Mohammed A. AlQahtani; Naflaa O. Alenazi; Abeer H. Alzahrani; Hayam A. Alobaid (Elsevier, 2021)
Objectives: Assessment of the effect of aging and bonding on the reparability of different temporary crown and bridge materials using a flowable resin composite. Methods: The materials used included two bis-acryl and two polymethylmethacrylate materials. The materials were aged either dry, in distilled water, or in a 75% ethanol/water solution. Each group was divided into three subgroups (n = 6) according to the bonding method: application of a universal adhesive, application of a universal primer followed by a universal adhesive, or no bonding. Materials were repaired with a light-cure flowable resin composite; then, they were subjected to thermocycling and tested by shear bond strength. The data were analysed using three-way ANOVA, one-way ANOVA, and Tukey post hoc tests (α = 0.05). Results: The shear bond strength was significantly higher for bis-acryl compared to polymethylmethacrylate materials (p < 0.001). In terms of aging conditions, shear bond strength was in the order of 75% ethanol/water solution < dry < water. The application of bonding agents significantly increased the shear bond strength of polymethylmethacrylate-based materials (p < 0.001). The difference between water and dry storage was insignificant (p = 0.558); however, storage in a 75% ethanol/water solution showed significantly lower values compared to both dry and water storage in most of experimental groups (p < 0.001). Polymethylmethacrylate-based materials mainly demonstrated adhesive failure, while bis-acryl materials predominantly showed cohesive failure. Conclusion: The bond strength of a light-cure flowable resin composite is significantly higher with bis-acryl compared to that with polymethylmethacrylate-based substrates. Aging in water does not have a significant effect; however, the 75% ethanol/water solution tends to negatively affect repairability. The application of different bonding agents positively affects the repair strength, especially for polymethylmethacrylate-based substrates.